Development of Learning Video using Guided Inquiry Methods on Circular Motion Subject to Improve Student Learning Outcomes - I Made Astra; Raihanati Raihanati; Syarifah Hafizah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractThis study aims to develop a learning video on circular motion subject as a physics learning media for high school students. The developed video is prepared based on the guided inquiry learning stage and completed with the Student Worksheet. This research used Research and Development (R&D) method, with ADDIE model. The developed video has been through feasibility test with the achievement percentage of 91.8% from material expert, 96.8% from media expert, and 85.9% from learning expert with excellent interpretation. The product trial results show the percentage of achievement of 81.7% from educator and 89.4% from learner. There is an increase of result was 54.4 to 79.8 with a normalized gain test of 0.56 Based on the result of feasibility test and experiment, it can be concluded that instructional video using guided inquiry method in circular motion subject is worth to be used as physics learning media in senior high school and improved students’ learning outcomes in medium category.AbstrakPenelitian ini bertujuan untuk mengembangkan video pembelajaran pada materi gerak melingkar sebagai media pembelajaran fisika untuk siswa SMA. Video yang dikembangkan disusun berdasarkan tahapan pembelajaran inkuiri terbimbing dan dilengkapi dengan Lembar Kerja Siswa (LKS). Penelitian ini menggunakan metode Research and Development (R&D), model ADDIE. Video yang dikembangkan telah melalui tahap uji kelayakan dengan persentase pencapaian 91.8% menurut ahli materi, 96.8% menurut ahli media, dan 85.9% menurut ahli pembelajaran dengan interpretasi sangat baik. Hasil uji coba produk menunjukkan persentase pencapaian 81.7% menurut pendidik dan 89.4% menurut peserta didik. Melalui uji coba kepada peserta didik, didapatkan kenaikan dari hasil pretest sebesar 54.4 menjadi 79.8 saat postest. Berdasarkan hasil uji kelayakan dan uji coba dapat disimpulkan bahwa video pembelajaran menggunakan metode inkuiri terbimbing pada materi gerak melingkar hasil pengembangan telah layak digunakan sebagai media pembelajaran fisika SMA.